Systemic Analysis of the Community and the Individual during the Paramilitaries’ Reintegration Process in Colombia (2003-2006) (2018)
Reintegration processes are as much a matter for the people who are going through them as for the society that is living such a conjuncture. After the analysis of the Ruta de Integración (Reintegration Route) applied between 2003 and 2006 for the paramilitary demobilization in Colombia, a arises about its implications at the moment in which someone faces a change of reality and about the way in which the society participates in this process. With a qualitative study, four life stories taken from the radio program “La Reintegración, el camino hacia la paz” (Reintegration, the path to peace) are analyzed and contrasted with the dimensions for reintegration: personal, habitability and citizenship. The mentioned dimensions are designed from an individual perspective on the role of ex-combatants and a communal approach regarding society’s disposition. As a result, we argue that it’s necessary to incorporate a systemic articulation for the process to be successful.